Mycobacterium caprae – the first case of the human infection in Poland - Monika Kozińska; Monika Krajewska-Wędzina; Ewa Augustynowicz-Kopeć (Annals of Agricultural and Environmental Medicine, 2020)
The strain of tuberculous mycobacteria called Mycobacterium caprae infects many wild and domestic animals; however, because of its zoonotic potential and possibility of transmission between animals and humans, it poses a serious threat to public health. Due to diagnostic limitations regarding identification of MTB strains available data regarding the incidence of M. caprae , human infection does not reflect the actual size of the problem. Despite the fact that the possible routes of tuberculosis transmission are known, the epidemiological map of this zoonosis remains underestimated. The progress in diagnostic techniques, application of advanced methods of mycobacterium genome differentiation and cooperation between scientists in the field of veterinary medicine and microbiology, have a profound meaning for understanding the phenomenon of bovine tuberculosis and its supervise its incidence. This is the first bacteriologically confirmed case of human infection of M. caprae in Poland.